Hydrogenation catalyst and preparation method and application thereof
By combining co-precipitation method with hydrothermal method, a low titanium oxide composite oxide support with low titanium oxide content was prepared, and active components and additives were introduced thereon, solving the high cost of using organic titanium-containing reagents in the preparation process of existing hydrogenation catalysts and the unsuitable suitable for industrial production, achieving efficient preparation of catalysts and excellent hydrogenation performance.
Patent Information
- Application Number
- CN202311347727.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-17
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-10-17
AI Technical Summary
The existing hydrogenation catalysts use organic titanium-containing reagents during the preparation process, which is costly and unsuitable for industrial production. At the same time, it cannot meet the needs of hydrodesulfurization reaction and aromatic hydrosaturation reaction at the same time.
The co-precipitation method and the hydrothermal method are used to prepare alumina-titanium oxide composite oxide support with low titanium oxide content, and active components and additives are introduced thereon, and the hydrogenation catalyst is prepared through gel formation reaction, aging reaction, hydrothermal treatment and calcination.
With inorganic titanium reagents and low titanium content, catalysts with good hydrodesulfurization activity and aromatic hydrosaturation properties are prepared, which simplifies the preparation process, reduces costs, and is suitable for industrial production.
Smart Images

Figure CN119838616A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogenation, and in particular to a hydrogenation catalyst and a preparation method and application thereof. Background Art
[0002] As oil resources continue to deteriorate and become heavier, the market demand for diversified and lighter petrochemical products is increasing. According to the composition characteristics of oil products, hydrogenation is used to achieve the hydrogenation saturation of polycyclic aromatic hydrocarbons, colloids and asphaltene, and the removal of heteroatoms and keeping the alkyl side chains intact as much as possible are the overall directions for improving the properties of oil products. Among them, catalysts are the core of hydrogenation technology. The development of new catalytic materials is the basis for improving catalyst performance. The carrier material needs to have a suitable pore size to provide a diffusion channel for reactant molecules, and at the same time have a large specific surface area to promote the dispersion of active metals on the carrier surface. TiO 2 The hydrogenation catalyst with TiO as the carrier showed excellent reaction performance during use. 2 Due to the limitations of its own pore structure and thermal stability, it has not been widely used in the field of hydrogenation catalysts. The titanium oxide-alumina composite oxide carrier obtained by combining titanium oxide with aluminum oxide can effectively overcome the limitation of TiO 2 The inherent limitations of the catalyst can be overcome while overcoming the problem that the metals loaded on the alumina carrier are difficult to reduce, thereby increasing the utilization rate of the active metals and enhancing the hydrogenation activity of the catalyst.
[0003] Patent application CN113649016A discloses a method for preparing a hydrogenation catalyst, wherein alumina, metatitanic acid and a solvent are mixed, subjected to high-energy ball milling and molding, and dried and calcined to obtain a titanium oxide-alumina carrier. A solution containing molybdenum and cobalt or nickel is impregnated into the titanium oxide-alumina composite carrier, and the hydrogenation catalyst is obtained after drying and calcining. The hydrogenation catalyst prepared by this method has the advantages of high low-temperature activity, good hydrogenation activity and stability at high space velocity.
[0004] Patent application CN109833891A discloses a method of using mesoporous TiO 2 -Al 2 O 3 A mesoporous alumina precursor is prepared by a template-directed method, and then titanium oxide, titanium isopropoxide or butyl titanate is introduced into the precursor solution, and a mesoporous TiO 2 -Al 2 O 3 Precursor, the precursor is mixed with alumina, an extrusion aid and a phosphate to form a strip, and then dried and calcined to obtain phosphorus-modified TiO 2 -Al 2 O 3The catalyst active components include metal oxides of group VIB, oxides of group VIII and oxides of group VA. The method can be used to prepare TiO2 rich in mesoporous 2 -Al 2 O 3 Carrier, effectively improving the desulfurization and denitrification capabilities of the catalyst.
[0005] Patent application CN1344586A discloses a supported nano-TiO 2 A composite carrier and a preparation method thereof, wherein the method comprises preparing a titanium sol by mixing butyl titanate with ethanol, water and nitric acid, adding the titanium sol into a slurry prepared by mixing pseudo-boehmite with water or anhydrous ethanol, drying the sample and calcining it at 200, 300, 400 and 500°C for 2 hours in sequence. The method can prepare a nano-TiO 2 Loaded on macroporous alumina, XRD results show that nano-TiO 2 The crystal form of the catalyst is anatase. Loading active components on the carrier can effectively improve the catalyst's hydrorefining catalytic activity.
[0006] The above method is complicated in the preparation of titanium oxide-alumina composite oxide carrier used in hydrogenation catalyst, and the production process is discontinuous. 2 The methods mostly use titanium-containing organic reagents, which are relatively costly and are not suitable for the industrial production of hydrogenation catalysts. The hydrogenation catalysts obtained cannot simultaneously meet the requirements of the hydrodesulfurization reaction and the aromatics hydrogenation saturation reaction. Summary of the invention
[0007] The purpose of the present invention is to overcome the problems existing in the prior art and provide a hydrogenation catalyst and a preparation method and application thereof. The method can prepare an aluminum oxide-titanium oxide composite oxide carrier with a low titanium oxide content and a specific crystal form as a hydrogenation catalyst carrier without using an organic titanium-containing reagent, which is more conducive to the industrial production of hydrogenation catalysts and improves the desulfurization reaction activity and aromatics hydrogenation saturation performance of the catalyst.
[0008] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a hydrogenation catalyst, wherein the method comprises the following steps:
[0009] (1) subjecting an acidic solution containing aluminum and titanium to a colloid reaction with an alkaline solution containing aluminum to obtain a solid colloid product;
[0010] (2) subjecting the solid gel-forming product obtained in step (1) to an aging reaction in the presence of a precipitant to obtain an aging reaction product;
[0011] (3) subjecting the aging reaction product obtained in step (2) to a hydrothermal treatment, and then to a first drying to obtain titanium-containing pseudo-boehmite, wherein the temperature of the hydrothermal treatment is higher than the temperature of the aging reaction;
[0012] (4) optionally shaping the titanium-containing pseudo-boehmite obtained in step (3), and then performing a second drying and a first calcination to obtain a titanium oxide-aluminum oxide composite oxide support;
[0013] (5) Introducing active components and auxiliary agents onto the titanium oxide-aluminum oxide composite oxide carrier obtained in step (4), and then performing a third drying and a second calcination to obtain a hydrogenation catalyst, wherein the active components are selected from at least one of the Group VIII metals and at least one of the Group VIB metals, and the auxiliary agents are selected from at least one of the Group VA elements.
[0014] The second aspect of the present invention provides a hydrogenation catalyst prepared by the preparation method described in the first aspect.
[0015] The third aspect of the present invention provides a use of the hydrogenation catalyst described in the second aspect in a hydrodesulfurization reaction or an aromatics hydrogenation saturation reaction.
[0016] The method provided by the present invention adopts a co-precipitation method and a hydrothermal method to prepare an aluminum oxide-titanium oxide composite oxide carrier with a low titanium oxide content and a specific crystal form as a hydrogenation catalyst carrier without using an organic titanium-containing reagent, which is more conducive to the industrial production of the hydrogenation catalyst and improves the hydrogenation desulfurization performance of the catalyst.
[0017] The method provided by the invention has simple process, cheap and readily available raw materials, easily controllable operating conditions and adjustable product properties.
[0018] The method provided by the present invention introduces active components and auxiliary agents on an alumina-titania composite oxide carrier for coordination, and the three work together to improve the reaction activity of the catalyst, which is more conducive to the hydrogenation reaction of aromatic hydrocarbons and difficult-to-remove sulfides, and improves the conversion rate of the reaction raw materials. The catalyst has both good hydrodesulfurization activity and aromatic hydrocarbon hydrogenation saturation performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is the XRD diagram of the alumina-titania composite oxide support prepared in Example 1 and Comparative Example 1;
[0020] Figure 2 It is the infrared skeleton diagram of the alumina-titania composite oxide support prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0021] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0022] A first aspect of the present invention provides a method for preparing a hydrogenation catalyst, wherein the method comprises the following steps:
[0023] (1) subjecting an acidic solution containing aluminum and titanium to a colloid reaction with an alkaline solution containing aluminum to obtain a solid colloid product;
[0024] (2) subjecting the solid gel-forming product obtained in step (1) to an aging reaction in the presence of a precipitant to obtain an aging reaction product;
[0025] (3) subjecting the aging reaction product obtained in step (2) to a hydrothermal treatment, and then to a first drying to obtain titanium-containing pseudo-boehmite, wherein the temperature of the hydrothermal treatment is higher than the temperature of the aging reaction;
[0026] (4) optionally shaping the titanium-containing pseudo-boehmite obtained in step (3), and then performing a second drying and a first calcination to obtain a titanium oxide-aluminum oxide composite oxide support;
[0027] (5) Introducing active components and auxiliary agents onto the titanium oxide-aluminum oxide composite oxide carrier obtained in step (4), and then performing a third drying and a second calcination to obtain a hydrogenation catalyst, wherein the active components are selected from at least one of the Group VIII metals and at least one of the Group VIB metals, and the auxiliary agents are selected from at least one of the Group VA elements.
[0028] In the present invention, there is no particular limitation on the method for preparing the acidic solution containing aluminum and titanium, as long as the acidic solution can be obtained by dissolving the titanium-containing compound in the aluminum solution. Preferably, in step (1), the acidic solution containing aluminum and titanium is obtained by dissolving the titanium-containing compound in the acidic aluminum solution.
[0029] In the present invention, there is no particular limitation on the type of titanium-containing compound, as long as it can meet the requirements of the colloid reaction. Preferably, the titanium-containing compound is titanyl sulfate and / or titanium sulfate. By selecting the titanium-containing compound within the above range to prepare the acidic solution containing titanium and aluminum for the colloid reaction, the use of organic titanium reagents is avoided, ensuring that the entire preparation process is simple and environmentally friendly.
[0030] In the present invention, there is no particular limitation on the type of the acidic aluminum solution. Preferably, the acidic aluminum solution is selected from at least one of an aluminum sulfate solution, an aluminum nitrate solution, and an aluminum chloride solution.
[0031] In the present invention, there is no particular limitation on the type of aluminum-containing alkaline solution, as long as a gelling reaction can be achieved. Preferably, in step (1), the aluminum-containing alkaline solution is a sodium aluminate solution and / or a potassium aluminate solution.
[0032] In the present invention, the ratio of titanium and aluminum is controlled by regulating the concentration of the acidic solution containing aluminum and titanium, and the control of the titanium content is achieved to prepare aluminum oxide-titanium oxide composite oxides in different ranges to meet different application scenarios. Preferably, in step (1), in the acidic solution containing aluminum and titanium, the concentration of the acidic solution containing aluminum and titanium is 35-120 g / L in terms of alumina, for example, 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L, 60 g / L, 65 g / L, 70 g / L, 75 g / L, 80 g / L, 85 g / L, 90 g / L, 95 g / L, 100 g / L, 110 g / L, 115 g / L, 120 g / L and values between any two groups.
[0033] Preferably, in step (1), the concentration of the acidic solution containing aluminum and titanium in terms of titanium oxide is 5-80 g / L, for example, 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L, 60 g / L, 65 g / L, 70 g / L, 75 g / L, 80 g / L and values between any two groups.
[0034] In the present invention, there is no particular limitation on the concentration of the aluminum-containing alkaline solution, as long as the requirements of the gelling reaction are met. Preferably, in step (1), the concentration of the aluminum-containing alkaline solution in terms of alumina is 20-300 g / L, for example, 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L, 110 g / L, 120 g / L, 130 g / L, 140 g / L, 150 g / L, 160 g / L, 170 g / L, 180 g / L, 190 g / L, 200 g / L, 210 g / L, 220 g / L, 230 g / L, 240 g / L, 250 g / L, 260 g / L, 270 g / L, 280 g / L, 290 g / L, 300 g / L and values between any two groups.
[0035] In the present invention, there is no particular limitation on the method of the gelling reaction, and it can be a method conventionally defined in the art. Preferably, in step (1), the gelling reaction is carried out in a continuous or intermittent manner, preferably in a continuous manner. On the one hand, the gelling reaction carried out in a continuous manner is more conducive to controlling the pH of the gelling reaction process and effectively improving the quality of the aluminum oxide-titanium oxide composite oxide. On the other hand, continuous operation can increase the processing volume per unit time and improve production efficiency.
[0036] The present invention has no particular limitation on the equipment for the gelling reaction, and it can be any conventional choice in the art. Specifically, for example, it can be carried out in a gelling tank.
[0037] According to a preferred specific embodiment of the present invention, the process of conducting a gelling reaction in a continuous manner in the present invention includes: adding a certain amount of deionized water in a gelling tank in advance, and introducing an acidic solution containing aluminum and titanium and an alkaline solution containing aluminum from the top of the gelling tank, so that the acidic solution containing aluminum and titanium and the alkaline solution containing aluminum are mixed and contacted to conduct a gelling reaction, and the slurry generated by the gelling reaction continuously flows out of the gelling tank, and the liquid level in the gelling tank is controlled to remain unchanged.
[0038] In the present invention, the conditions for the gelling reaction are relatively wide. Preferably, in step (1), the conditions for the gelling reaction include: a temperature of 50-70°C and a pH value of 4-7. In this preferred embodiment, it is more conducive to improving the quality of the aluminum oxide-titanium oxide composite oxide. In the present invention, during the gelling reaction, the pH value should not be too high. Too high a gelling reaction pH will result in low pore volume and specific surface area of the titanium aluminum composite oxide product; the pH of the gelling reaction should not be too low, because a lower gelling reaction pH is likely to result in large differences in the generation rates of hydrated oxides of aluminum and titanium, which is not conducive to the uniform dispersion of titanium in aluminum oxide. In the present invention, there is no particular limitation on the method for controlling the pH. For example, the flow rate of the acidic solution containing aluminum and titanium and the precipitant can be adjusted. In the present invention, there is no particular limitation on the flow rate of the acidic solution containing aluminum and titanium and the precipitant, as long as the pH value of the gelling reaction is met.
[0039] In the present invention, the pH value of the reaction system is regulated by adding a precipitant, so that the slurry of the solid gelled product obtained in step (1) after beating is subjected to an aging reaction. The present invention has a wide range of selection of precipitants. Preferably, in step (2), the precipitant is selected from a compound containing an alkali metal, preferably selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate. In the present invention, there is no particular limitation on the amount of the precipitant, and it is sufficient to limit the pH value required for the aging reaction. Those skilled in the art can select according to actual needs.
[0040] In the present invention, the range of conditions for the aging reaction is relatively wide. Preferably, in step (2), the conditions for the aging reaction include: a temperature of 60-98°C, a time of 4-9h, and a pH value of 7-11;
[0041] Further preferably, in step (2), the aging reaction conditions include: temperature of 70-95°C, time of 5-8h, and pH of 7.5-10. By controlling the aging reaction conditions, the pore structure of the alumina-titania composite oxide can be regulated to improve the quality of the alumina-titania composite oxide.
[0042] In the present invention, preferably, after the aging treatment, step (2) further comprises solid-liquid separation of the aged product to obtain a solid aged product. In the present invention, the solid-liquid separation is a conventional operation in the art, specifically, for example, at least one of sedimentation, filtration and centrifugal separation, and those skilled in the art can select according to actual needs.
[0043] In the present invention, preferably, the temperature of the hydrothermal treatment is 10-100°C higher than the temperature of the aging reaction, preferably 10-80°C higher, more preferably 20-70°C higher, for example, it can be 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C and values between any two groups. By controlling the temperature of the aging reaction and the hydrothermal treatment, the pore concentration of the aluminum oxide-titanium oxide composite oxide can be increased, and anatase crystal form can be obtained. When the temperature difference between the two is not within the above preferred range, the grain size of the aluminum oxide-titanium oxide composite oxide is larger, which affects the specific surface area and the most probable pore size of the composite oxide material.
[0044] In the present invention, preferably, before the hydrothermal treatment, step (3) further comprises washing the solid aged product. In the present invention, the washing operation is a conventional operation in the art, and it is only necessary to reduce the content of impurity ions (such as residual sodium and sulfate) in the solid aged product, for example, so that the content of sodium oxide in the obtained aluminum oxide-titanium oxide composite oxide is less than 0.1% by weight, preferably less than 0.06% by weight, and more preferably 0.01-0.05% by weight.
[0045] In the present invention, preferably, step (3) comprises: adding water (preferably deionized water) to the solid aged product after the aging treatment, beating the solid aged product, and then performing hydrothermal treatment. In the present invention, the amount of water used is such that the concentration of the slurry obtained after beating the solid aged product is 50-180 g / L, preferably 70-150 g / L, based on the weight of the oxides (aluminum oxide + titanium oxide).
[0046] In the present invention, preferably, the method does not use an organic titanium-containing reagent. The present invention prepares the aluminum oxide-titanium oxide composite oxide material by coprecipitation and hydrothermal treatment, has a simple reaction process, is easy to operate, uses cheap and readily available raw materials, does not require organic reagents, and has an environmentally friendly production process.
[0047] Under the premise that the temperature of the hydrothermal treatment is higher than the temperature of the aging reaction, the selection range of the conditions for the hydrothermal treatment is relatively wide, in order to further optimize the pore structure characteristics of the alumina-titania composite oxide. Preferably, in step (3), the conditions for the hydrothermal treatment include: a temperature of 100-180°C and a time of 2-9h. In the present invention, the hydrothermal treatment can change the existence state of titanium dioxide on alumina. The coprecipitation method is combined with the hydrothermal method, which not only improves the pore concentration of the alumina-titania composite oxide and makes the most probable pore size fall within an appropriate range, but also allows the titanium dioxide dispersed in the alumina skeleton to aggregate to form anatase, and obtains anatase-γ-Al with a low titanium dioxide content. 2 O 3 carrier.
[0048] In the present invention, the first drying conditions can be selected in a wide range. Preferably, the first drying conditions include: a temperature of 60-200°C, more preferably 100-160°C.
[0049] In the present invention, there is no particular limitation on the molding method described in step (4). Preferably, the molding described in step (4) includes: mixing the titanium-containing pseudo-boehmite obtained in step (3) with an optional extrusion aid, an adhesive and water to form the mixture, and then performing a second drying and calcining to obtain a titanium oxide-aluminum oxide composite oxide carrier. In the present invention, the extrusion aid used in the molding process is an extrusion aid conventionally defined in the art, such as sesbania powder and cellulose. In the present invention, the extrusion aid used in the molding process is an adhesive conventionally defined in the art, such as nitric acid, acetic acid, and citric acid. The present invention does not specifically limit the amount of extrusion aid, adhesive and water used in the molding process, and those skilled in the art can choose according to actual needs. In the present invention, the second drying is a conventional method, such as drying in an oven, a mesh belt kiln and a fluidized bed. When drying is performed by a heating method, the second drying temperature is preferably 50-200°C and the second drying time is 0.5-6 hours. It is further preferred that the second drying temperature is 60-150°C and the second drying time is 2-4 hours. In the present invention, the calcination method and conditions are the conventional methods and conditions used in the preparation of catalyst carriers, such as using a mesh belt kiln, a vertical furnace and a converter for calcination. Preferably, in step (4), the first calcination conditions include: a temperature of 300-800°C and a time of 1-6 hours; more preferably, in step (4), the first calcination conditions include: a temperature of 400-600°C and a time of 2-4 hours.
[0050] In the present invention, preferably, the amount of the acidic solution containing aluminum and titanium and the alkaline solution containing aluminum is such that the content of aluminum oxide in the prepared aluminum oxide-titanium oxide composite oxide carrier is 70-99% by weight, preferably 75-95% by weight, and the content of titanium oxide is 1-30% by weight, preferably 4-25% by weight, based on the total amount of the aluminum oxide-titanium oxide composite oxide carrier. It should be noted that a small amount of impurities may exist in the aluminum oxide-titanium oxide composite oxide carrier. Therefore, when impurities exist, the contents of aluminum oxide, titanium oxide and impurities satisfy that the sum is equal to 100%. In the present invention, the type of impurities is not specifically limited, for example, it can be SO 3 、Na 2 O etc.
[0051] In the present invention, the composition of the alumina-titania composite oxide carrier is determined by measuring the characteristic spectral lines of each element using a 3271 X-ray fluorescence spectrometer produced by Rigaku Corporation, and the element content of the alumina-titania composite oxide carrier is semi-quantitatively analyzed using an external standard method.
[0052] In the present invention, preferably, the titanium oxide is anatase type and the aluminum oxide is γ crystalline. The method of the present invention can realize the preparation of anatase type aluminum oxide-titanium oxide composite oxide carrier in the absence of organic titanium reagent and low titanium content.
[0053] In the present invention, the crystal structure of the aluminum oxide-titanium oxide composite oxide is measured by using a Philips XPERT series X-ray powder diffractometer.
[0054] The alumina-titania composite oxide carrier provided by the present invention has a high pore concentration, which is conducive to the hydrogenation reaction. Preferably, the alumina-titania composite oxide carrier has a pore volume of 0.4-1 mL / g and a specific surface area of 150-400 m 2 / g, the most probable pore size is 5-13nm; further preferably, the pore volume of the alumina-titania composite oxide carrier is 0.6-0.8mL / g, and the specific surface area is 200-300m 2 / g, and the most probable pore size is 7-12nm.
[0055] In the present invention, the pore structure characteristics of the aluminum oxide-titanium oxide composite oxide are measured by N adsorption on a Micromeritics ASAP2420 adsorption instrument. 2 Adsorption-desorption characterization was measured.
[0056] In the present invention, preferably, in step (5), the active component is selected from cobalt and / or nickel and molybdenum and / or tungsten.
[0057] In the present invention, preferably, the active components are provided by the precursors of the active components, further preferably by the soluble compounds of the active components, and further preferably by at least one of nickel nitrate, nickel acetate, nickel sulfate, basic nickel carbonate, nickel chloride, cobalt sulfate and cobalt nitrate and at least one of sodium molybdate, ammonium paramolybdate, molybdenum oxide, sodium tungstate, ammonium tungstate and ammonium metatungstate.
[0058] In the present invention, preferably, in step (5), the auxiliary agent is phosphorus.
[0059] In the present invention, preferably, the auxiliary agent is provided by a compound containing auxiliary agent elements, and more preferably provided by at least one of phosphoric acid, ammonium phosphate, ammonium hydrogen phosphate, diammonium hydrogen phosphate, sodium phosphate and potassium phosphate.
[0060] In the present invention, there is no particular limitation on the introduction method of active components and auxiliary agents. Under the premise that the metal selected from at least one Group VIB and at least one Group VIII metal and / or at least one Group VA component is loaded on the titanium oxide-alumina composite oxide carrier, any known hydrogenation catalyst preparation method can be used for preparation, such as impregnation method, coprecipitation method, preferably impregnation method. According to a specific embodiment of the present invention, a solution containing active components of Group VIII and Group VIB and auxiliary agents is contacted with an alumina-titanium oxide composite oxide carrier, and then a third drying and a second calcination are performed to obtain a hydrogenation catalyst. In the present invention, the conditions for the third drying are the conditions commonly used in the preparation of such catalysts, such as a drying temperature of 80-200°C, preferably 100-200°C, and a drying time of 1-24 hours, preferably 2-12 hours. In the present invention, the selection range of the conditions for the second calcination is relatively wide. Preferably, in step (5), the conditions for the second calcination include: a temperature of 250-600°C and a time of 1-6h; further preferably, in step (5), the conditions for the second calcination include: a temperature of 300-500°C and a time of 2-4h.
[0061] In the present invention, the amounts of the titanium oxide-aluminum oxide composite oxide carrier, active components and additives are such that, in the prepared hydrogenation catalyst, based on the total amount of the hydrogenation catalyst, the content of the Group VIII metal in terms of oxide is 0.5-10% by weight, preferably 1.5-5% by weight, the content of the Group VIB metal in terms of oxide is 5-35% by weight, preferably 6-30% by weight, and the content of the Group VA element in terms of oxide is 1-6% by weight, preferably 2-5% by weight.
[0062] In the present invention, the content of each component in the hydrogenation catalyst is measured by measuring the characteristic spectrum of each element using a 3271 X-ray fluorescence spectrometer produced by Rigaku Corporation of Japan, and the element content of the aluminum oxide-titanium oxide composite oxide is measured by semi-quantitative analysis using an external standard method.
[0063] The second aspect of the present invention provides a hydrogenation catalyst prepared by the preparation method described in the first aspect.
[0064] In the present invention, preferably, the pore volume of the hydrogenation catalyst is 0.4-0.7 mL / g and the specific surface area is 170-220 m 2 / g, and the most probable pore size is 7-11nm.
[0065] In the present invention, the pore structure characteristics of the hydrogenation catalyst are measured by N adsorption on a Micromeritics ASAP 2420 adsorption instrument. 2 Adsorption-desorption characterization was measured.
[0066] The third aspect of the present invention provides a use of the hydrogenation catalyst described in the second aspect in a hydrodesulfurization reaction or an aromatics hydrogenation saturation reaction.
[0067] The hydrogenation catalyst provided by the invention has both desulfurization reaction activity and aromatic hydrocarbon hydrogenation saturation performance.
[0068] The hydrodesulfurization reaction conditions for difficult-to-remove sulfides provided by the present invention are the conditions conventionally defined in the art. Preferably, the hydrodesulfurization reaction conditions are: reaction temperature 240-360°C, preferably 260-300°C; reaction pressure 3-6MPa, preferably 4-5MPa; volume space velocity 10-80h -1 , preferably 20-60h -1 ; Hydrogen to oil volume ratio 200-1000, preferably 300-600.
[0069] The reaction conditions for the hydrogenation of aromatics provided by the present invention are the conditions conventionally defined in the art. Preferably, the conditions for the hydrogenation of aromatics are: reaction temperature 200-320°C, preferably 240-300°C; reaction pressure 3-6MPa, preferably 4-5MPa; volume space velocity 10-80h -1 , preferably 20-60h -1 ; The volume ratio of hydrogen to oil is 200-1000, preferably 300-600.
[0070] In the present invention, the hydrogenation reaction can be carried out in any reactor that is sufficient to allow the crude oil to contact and react with the aforementioned hydrogenation catalyst under the hydrogenation reaction conditions, for example, in the micro fixed bed reactor.
[0071] In the present invention, according to the conventional method in the art, the hydrogenation catalyst for hydrodesulfurization reaction or aromatic hydrocarbon hydrogenation saturation reaction can be pre-sulfurized with sulfur, hydrogen sulfide or sulfur-containing raw materials in the presence of hydrogen at a temperature of 70-360° C. before use. The pre-sulfurization treatment can be carried out outside the device or in situ in the device. The present invention does not particularly limit the specific operation mode of pre-sulfurization, and those skilled in the art can select it according to actual needs.
[0072] The present invention will be described in detail below by way of examples. In the following examples, all raw materials used are commercially available unless otherwise specified.
[0073] The composition of the alumina-titanium oxide composite oxide carrier was determined by the characteristic spectral lines of each element using the 3271 X-ray fluorescence spectrometer produced by Rigaku Corporation. The element content of the titanium-aluminum composite oxide was semi-quantitatively analyzed by the external standard method to obtain the Al content in the sample. 2 O 3 、TiO 2 、SO 3 、Na 2 O and other components.
[0074] N 2 The adsorption and desorption characterization methods were as follows: N 2 For adsorption-desorption characterization, about 0.3 g of the alumina-titania composite oxide carrier was pretreated at 350° C. under vacuum conditions for 10 hours before testing.
[0075] The crystal form characterization method of the aluminum oxide-titanium oxide composite oxide is as follows: a certain amount of the aluminum oxide-titanium oxide composite oxide carrier is ground into powder, pressed into a sheet, and the crystal form of the sample is determined by a Philips XPERT series X-ray powder diffractometer. The test conditions are: Cu Kα ray (Kα = 0.154nm), working current 30mA, working voltage 40kV, Ni filter, scanning range 2θ = 5°-70°.
[0076] The infrared skeleton characterization method of the alumina-titania composite oxide carrier is as follows: a certain amount of alumina-titania composite oxide carrier is ground into powder, KBr is added and pressed into a sheet, and a Nicolet 6700 infrared spectrometer produced by Thermo Fisher is used with a resolution of 4 cm -1 , scanning range 4000-400cm -1 , scanned 32 times, and the infrared spectrum of aluminum oxide-titanium oxide composite oxide was obtained by single-point attenuated total reflection method.
[0077] The radial crushing strength test method of the alumina-titania composite oxide carrier is as follows: a 5 mm carrier is horizontally placed between two platforms of a particle strength tester, a load is uniformly applied to it until the carrier is destroyed, and the applied pressure when the particles are crushed is recorded.
[0078] Example 1
[0079] (1) 3 L of deionized water is added to a gelling tank in advance, titanyl sulfate is added to an aluminum sulfate solution to prepare an acidic solution containing aluminum and titanium, the acidic solution containing aluminum and titanium and a sodium aluminate solution are introduced from the top of the gelling tank, and the acidic solution containing aluminum and titanium and the sodium aluminate solution are mixed in the gelling tank to perform a gelling reaction, and the slurry after the gelling reaction flows out from the overflow pipe of the gelling tank, and the liquid level in the gelling tank remains unchanged. When the deionized water added in advance is replaced by the slurry after the gelling reaction, the slurry is collected, and then filtered to obtain a filter cake (solid gelling product);
[0080] Among them, the concentration of sodium aluminate solution (calculated as alumina) is 200g / L, the flow rate is 42g / min, the titanium oxide concentration in the acidic solution containing aluminum and titanium is 12.89g / L, and the alumina concentration is 58g / L. By adjusting the flow rate of the acidic solution containing aluminum and titanium to 115-125g / min, the pH value of the gelation reaction process is about 6.3, and the temperature of the gelation reaction is 60°C.
[0081] (2) The gelling reaction product is subjected to an aging treatment, and the pH of the aging treatment is adjusted by adding a sodium carbonate solution. The aging treatment conditions are pH 9.0, temperature 90° C., and time 6 h.
[0082] (3) The aged mixture was filtered and washed in sequence to remove residual sodium and sulfate, and then the obtained filter cake (solid aged product) was added to deionized water for slurrying. The concentration of the obtained slurry was 130 g / L based on the weight of the titanium oxide-aluminum oxide composite oxide. The obtained slurry was hydrothermally treated at a temperature of 150° C. for 4 hours. After the hydrothermal treatment, titanium-containing pseudo-boehmite A1 was obtained after spray drying.
[0083] (4) Take 100 g of titanium-containing pseudo-boehmite A1 and 3 g of sesbania powder and mix them evenly. At room temperature, mix the mixture with 85 ml of 1.65% nitric acid aqueous solution, continue to knead it into a plastic body on a twin-screw extruder, and extrude it into butterfly-shaped strips of Φ1.4 mm. After the wet strips are dried at 120°C for 4 hours, they are calcined at 550°C for 3 hours to obtain carrier Z1. The composition and properties of carrier Z1 are shown in Table 1.
[0084] (5) Take 10 g of the carrier and add 6.6 ml of MoO 3 The content is 278 g / L, the NiO content is 67.1 g / L, and the P2 O 5 The catalyst C1 was obtained by impregnating a mixed solution of molybdenum oxide, basic nickel carbonate and phosphoric acid with a content of 57.5 g / L for 2 hours, drying at 120°C for 2 hours and calcining at 400°C for 3 hours.
[0085] from Figure 1 It can be seen that in Example 1, titanium oxide is in anatase crystal form (titanium oxide has diffraction peaks at 25.3°, 48.1°, 54°, and 55.1°, indicating that titanium oxide is in anatase crystal form), and aluminum oxide is in γ-Al 2 O 3 Crystal form (alumina has diffraction peaks at 36°, 45°, and 67°, indicating that alumina is γ-Al 2 O 3 Crystal form). Figure 2 The infrared skeleton analysis results of Example 1 and Comparative Example 1 are shown in Figure 1, where 1100 cm -1 The peak at is the characteristic peak of Al-O bond. Figure 2 It can be seen that the characteristic vibration peak of the Al-O bond in Example 1 disappears, indicating that the Ti in Example 1 partially replaces the Al in the alumina structure, affecting the chemical environment around the Al atoms, and further affecting the reaction activity of the catalyst prepared with the alumina-titania composite oxide carrier.
[0086] Comparative Example 1
[0087] This comparative example adopts the preparation method in the existing technical document ("Effects of the addition of titania on the ethermal characterization of alumina-supported palladium", Journal of Molecular Catalysis A, 2002, 180, 285-291) to prepare titanium oxide-aluminum oxide composite oxide. 2 O 3 (Sinopec Changling Catalyst Co., Ltd.), and 7.74g of isopropyl titanate was dissolved in propanol, quantified to 15mL and stirred thoroughly. 2 O 3 The alumina-titania composite oxide support DS1 was obtained after being dispersed in the isopropanol solution of isopropyl titanate, dried at 110°C overnight, and calcined at 550°C for 3 hours.
[0088] from Figure 1 It can be seen that the titanium oxide in the composite oxide carrier prepared by this method is in anatase crystal form, and the aluminum oxide is in γ-Al 2 O 3 Crystal form. Figure 2 The infrared skeleton analysis results show that compared with pure alumina support, the -1 The characteristic peak of the Al-O bond did not change, indicating that the organic impregnation method would not affect the skeleton structure of alumina.
[0089] Take 20 g of carrier DS1 and add 14.8 ml of MoO 3 The content is 248 g / L, the NiO content is 59.87 g / L, and the P 2 O 5 The catalyst DC1 was obtained by impregnating a mixed solution of molybdenum oxide, basic nickel carbonate and phosphoric acid with a content of 51.32 g / L for 2 hours, drying at 120°C for 2 hours and calcining at 400°C for 3 hours.
[0090] Example 2
[0091] According to the method of Example 1, in step (1), the concentration of titanium oxide in the acidic solution containing aluminum and titanium is 20.67 g / L, the concentration of aluminum oxide is 45.76 g / L, and the flow rate is 110-120 g / min. The other conditions are the same as those of Example 1.
[0092] (2) Same as Example 1.
[0093] (3) The aged mixture is filtered and washed in sequence to remove residual sodium and sulfate, and then the obtained filter cake (solid aged product) is added to deionized water for slurrying. The concentration of the obtained slurry is 130 g / L based on the weight of the titanium oxide-aluminum oxide composite oxide. The obtained slurry is hydrothermally treated at 150°C for 4 hours, filtered, and dried at 120°C for 6 hours to obtain titanium-containing pseudo-boehmite A2.
[0094] (4) 100 g of titanium-containing pseudo-boehmite A2 and 3 g of sesbania powder were mixed evenly, and the mixture was mixed evenly with 105 ml of 1% nitric acid aqueous solution at room temperature, and then kneaded into a plastic body on a twin-screw extruder, and then extruded into butterfly-shaped strips of Φ1.4 mm. The wet strips were dried at 120°C for 4 hours and then calcined at 600°C for 3 hours to obtain carrier Z2. The composition and properties of carrier Z2 are shown in Table 1. The alumina in Example 2 is the same as in Example 1 and is in the form of γ-Al 2 O 3 Crystal form.
[0095] (5) Take 20 g of the carrier and add 13.8 ml of MoO 3 The content is 193.12 g / L, the CoO content is 45.24 g / L, and the P 2 O 5 The catalyst C2 was obtained by impregnating a mixed solution of ammonium molybdate, cobalt nitrate and phosphoric acid with a content of 52.19 g / L for 2 hours, drying at 120°C for 2 hours, and calcining at 400°C for 3 hours.
[0096] Example 3
[0097] According to the method of Example 2, steps (1) and (2) are the same as those of Example 2;
[0098] (3) The aged mixture is filtered and washed in sequence to remove residual sodium and sulfate, and then the obtained filter cake (solid aged product) is added to deionized water for slurrying. The concentration of the obtained slurry is 130 g / L based on the weight of the titanium oxide-aluminum oxide composite oxide. The obtained slurry is hydrothermally treated at 130°C for 4 hours, filtered, and dried at 120°C for 6 hours to obtain titanium-containing pseudo-boehmite A3.
[0099] (4) 100 g of titanium-containing pseudo-boehmite A3 and 3 g of sesbania powder were mixed evenly, and the mixture was mixed evenly with 105 ml of 2% nitric acid aqueous solution at room temperature, and continued to be kneaded into a plastic body on a twin-screw extruder, and then extruded into butterfly-shaped strips of Φ1.4 mm. The wet strips were dried at 120°C for 4 hours and then calcined at 600°C for 3 hours to obtain carrier Z3. The composition and properties of carrier Z3 are shown in Table 1. The alumina in Example 3 is the same as in Example 1 and is in the form of γ-Al 2 O 3 Crystal form.
[0100] (5) Take 20 g of the carrier and add 14.4 ml of MoO 3 The content is 185.07 g / L, the CoO content is 43.35 g / L, and the P 2 O 5 The catalyst C3 was obtained by impregnating a mixed solution of ammonium molybdate, cobalt nitrate and phosphoric acid with a content of 50.02 g / L for 2 hours, drying at 120°C for 2 hours, and calcining at 400°C for 3 hours.
[0101] Example 4
[0102] According to the method of Example 2, steps (1) and (2) are the same as those of Example 2;
[0103] (3) The aged mixture is filtered and washed in sequence to remove residual sodium and sulfate, and then the obtained filter cake (solid aged product) is added to deionized water for slurrying. The concentration of the obtained slurry is 130 g / L based on the weight of the titanium oxide-aluminum oxide composite oxide. The obtained slurry is hydrothermally treated at 110° C. for 4 h to obtain titanium-containing pseudo-boehmite A4.
[0104] (4) 100 g of titanium-containing pseudo-boehmite A4 and 3 g of sesbania powder were mixed evenly, and the mixture was mixed evenly with 105 ml of 2.5% nitric acid aqueous solution at room temperature, and then kneaded into a plastic body on a twin-screw extruder, and then extruded into butterfly-shaped strips of Φ1.4 mm. The wet strips were dried at 120°C for 4 hours and then calcined at 600°C for 3 hours to obtain carrier Z4. The composition and properties of carrier Z4 are shown in Table 1. The alumina in Example 4 is the same as in Example 1 and is in the form of γ-Al 2 O 3 Crystal form.
[0105] (5) Take 20 g of the carrier and add 14.8 ml of MoO 3 The content is 180.07 g / L, the CoO content is 42.18 g / L, and the P 2 O 5 The catalyst C4 was obtained by impregnating a mixed solution of ammonium molybdate, cobalt nitrate and phosphoric acid with a content of 48.67 g / L for 2 hours, drying at 120°C for 2 hours and calcining at 400°C for 3 hours.
[0106] Example 5
[0107] According to the method of Example 2, steps (1) and (3) are the same as those of Example 2, except that the aging treatment temperature in step (2) is 60° C. The composition and properties of carrier Z5 are shown in Table 1.
[0108] (4) Take 100 g of titanium-containing pseudo-boehmite A5 and 3 g of sesbania powder and mix them evenly. At room temperature, mix the mixture with 70 ml of 2% nitric acid aqueous solution, continue to knead it into a plastic body on a twin-screw extruder, and extrude it into butterfly-shaped strips of Φ1.4 mm. After the wet strips are dried at 120°C for 4 hours, they are calcined at 600°C for 3 hours to obtain carrier Z5. The composition and properties of carrier Z5 are shown in Table 1.
[0109] The aluminum oxide in Example 5 is the same as that in Example 1 and is γ-Al 2 O 3 Crystal form.
[0110] (5) Take 20 g of carrier Z5 and add 11.6 ml of MoO 3 The content is 229.7 g / L, the CoO content is 53.81 g / L, and the P 2 O 5 The catalyst C5 was obtained by impregnating a mixed solution of ammonium molybdate, cobalt nitrate and phosphoric acid with a content of 62.09 g / L for 2 hours, drying at 120°C for 2 hours, and calcining at 400°C for 3 hours.
[0111] Example 6
[0112] According to the method of Example 1, in step (1), the concentration of titanium oxide in the acidic solution containing aluminum and titanium is 31.75 g / L, and the concentration of aluminum oxide is 46.64 g / L. The remaining conditions are the same as those of Example 1.
[0113] (2) Same as Example 1.
[0114] (3) The aged mixture is filtered and washed in sequence to remove residual sodium and sulfate, and then the obtained filter cake (solid aged product) is added to deionized water for slurrying. The concentration of the obtained slurry is 130 g / L based on the weight of the titanium oxide-aluminum oxide composite oxide. The obtained slurry is hydrothermally treated at 120°C for 4 hours, filtered, and dried at 120°C for 6 hours to obtain titanium-containing pseudo-boehmite A6.
[0115] (4) Take 100 g of titanium-containing pseudo-boehmite A6 and 3 g of sesbania powder and mix them evenly. At room temperature, mix the mixture with 80 ml of 2% nitric acid aqueous solution, continue to knead it into a plastic body on a twin-screw extruder, and extrude it into butterfly-shaped strips of Φ1.4 mm. After the wet strips are dried at 120°C for 4 hours, they are calcined at 600°C for 3 hours to obtain carrier Z6. The composition and properties of carrier Z6 are shown in Table 1.
[0116] The aluminum oxide in Example 6 is the same as that in Example 1 and is γ-Al 2 O 3 Crystal form.
[0117] (5) Take 20 g of the carrier and add 12.4 ml of MoO 3 The content is 296 g / L, the NiO content is 71.46 g / L, and the P 2 O 5 The catalyst C6 was obtained by impregnating a mixed solution of ammonium molybdate, cobalt nitrate and phosphoric acid with a content of 61.25 g / L for 2 hours, drying at 120°C for 2 hours, and calcining at 400°C for 3 hours.
[0118] Example 7
[0119] (1) The method of Example 1 is followed, except that in step (1), an acidic solution containing aluminum and titanium with different titanium oxide contents is used. Specifically, the titanium oxide concentration is 6.11 g / L, the aluminum oxide concentration is 58 g / L, and the flow rate is 120-130 g / min.
[0120] (2) subjecting the gelling reaction product to an aging treatment, wherein the aging treatment conditions are as follows: pH 8.0, temperature 70° C., time 8 h, and the concentration of the aging mixture is 70 g / L based on titanium oxide-aluminum oxide.
[0121] (3) The aged mixture was filtered and washed in sequence to remove residual sodium and sulfate, and then the obtained filter cake (solid aged product) was added to deionized water for slurrying. The concentration of the obtained slurry was 130 g / L based on titanium oxide-aluminum oxide. The obtained slurry was hydrothermally treated at a temperature of 170° C. for 4 hours. After the hydrothermal treatment, the titanium-containing pseudo-boehmite A7 was obtained after spray drying and calcination at 600° C. for 3 hours.
[0122] (4) 100 g of titanium-containing pseudo-boehmite A7 and 3 g of sesbania powder were mixed evenly. The mixture was mixed evenly with 90 ml of 2.5% nitric acid aqueous solution at room temperature. After being kneaded into a plastic body on a twin-screw extruder, it was extruded into butterfly-shaped strips of Φ1.4 mm. The wet strips were dried at 120°C for 4 hours and then calcined at 550°C for 3 hours to obtain carrier Z7. The composition and properties of carrier Z7 are shown in Table 1. The alumina in Example 7 is the same as in Example 1 and is in the form of γ-Al 2 O 3 Crystal form.
[0123] (5) Take 20 g of the carrier and add 14.4 ml of MoO 3 The content is 254.92 g / L, the NiO content is 61.53 g / L, and the P 2 O 5 The catalyst C7 was obtained by impregnating a mixed solution of molybdenum oxide, basic nickel carbonate and phosphoric acid with a content of 52.74 g / L for 2 hours, drying at 120°C for 2 hours and calcining at 500°C for 3 hours.
[0124] Comparative Example 2
[0125] According to the method of comparative example 1, take γ-Al 2 O 3 (Sinopec Changling Catalyst Co., Ltd.), and 15.48g of isopropyl titanate was dissolved in propanol, quantified to 15mL and stirred thoroughly. 2 O 3 The alumina-titania composite oxide support DS2 was obtained after being dispersed in the isopropyl alcohol solution of isopropyl titanate, dried at 110°C overnight, and calcined at 550°C for 3 hours.
[0126] Take 20 g of carrier DS2 and add 14 ml of MoO 3 The content is 190.4 g / L, the CoO content is 44.6 g / L, and the P 2 O 5 The catalyst D2 was obtained by impregnating a mixed solution of molybdenum oxide, basic nickel carbonate and phosphoric acid with a content of 51.45 g / L for 2 hours, drying at 120°C for 2 hours, and calcining at 400°C for 3 hours.
[0127] Comparative Example 3
[0128] This embodiment adopts the titration precipitation method in patent application CN111050904A to prepare titanium oxide-aluminum oxide composite oxide carrier. Sodium aluminate is diluted in water, and aluminum sulfate and titanyl sulfate are added under vigorous stirring and heating at 60°C, and the final pH value is 6.5. The pH is adjusted to 7.2 using NaOH, and the mixture is aged at 60°C for 1 hour under stirring. The filter cake is re-slurried with water, adjusted to pH 10 with ammonia water, and aged at 95°C for 1 hour under stirring. Then, the slurry is filtered and washed with water to remove excess ammonia, dried, extruded and roasted at 650°C for 1 hour under an air flow of 10mL / min and 25% (volume ratio) steam to obtain an aluminum oxide-titanium oxide composite oxide carrier DS3. The composition and properties of the aluminum oxide-titanium oxide composite oxide carrier DS3 are shown in Table 1.
[0129] The remaining steps are the same as in Example 1 to obtain catalyst D3.
[0130] The compositions and properties of the catalysts prepared in the above examples and comparative examples are shown in Table 2.
[0131] Table 1
[0132]
[0133] Note: There are trace impurities during the carrier synthesis and analysis process.
[0134] From the results in Table 1, it can be seen that Examples 1-7 prepared by the method of the present invention all have anatase-γ-Al 2 O 3 When the preparation conditions are within the preferred range described in the present invention, the alumina-titania composite oxide carrier has a better specific surface area and the most probable pore size, and the carrier strength is higher. Compared with the comparative example, the raw materials for preparing the alumina-titania composite oxide material by the method described in the present invention are cheap and easy to obtain, the preparation process is simple, and the process is short to obtain anatase-γ-Al with low titanium content. 2 O 3 Crystalline composite oxide materials.
[0135] Table 2
[0136]
[0137] It can be seen from the results in Table 2 that when the preparation conditions are within the preferred range described in the present invention, the catalyst using the aluminum oxide-titanium oxide composite oxide as a carrier has a better specific surface area and most probable pore size.
[0138] Test Example 1
[0139] The catalysts prepared in the above examples and comparative examples were used in a fixed bed continuous flow microreactor, with n-decane solution containing 0.45% 4,6-DMDBT (mass fraction) and 0.45% decalin (mass fraction) as the raw oil. The catalysts needed to be pre-sulfurized before the reaction, and the sulfurized oil was 5% CS 2 The reaction conditions of 4,6-DMDBT are as follows: the reaction temperature is 280℃, the reaction pressure is 4MPa, the hydrogen flow rate is 100mL / min, the reaction oil flow rate is 0.2mL / min, and the volume space velocity is 40h -1 After the system was stabilized, the product condensate was collected and the product composition was analyzed by GC-MS. The reaction results are shown in Table 3.
[0140] Test Example 2
[0141] The catalysts prepared in the above examples and comparative examples were used in a fixed bed continuous flow microreactor, with n-decane solution containing 1% decalin (mass fraction) and 1% pyrene (mass fraction) as the raw oil. The catalysts needed to be pre-sulfurized before the reaction, and the sulfurized oil was 5% CS 2 (mass fraction) of cyclohexane solution, the sulfidation temperature is 360℃, the hydrogen flow rate is 365mL / min, the sulfidation oil flow rate is 0.4mL / min, and the sulfidation pressure is 4MPa. After the sulfidation is completed, switch to reaction oil. The reaction conditions of pyrene are reaction temperature of 240℃, reaction pressure of 4MPa, hydrogen flow rate of 100mL / min, reaction oil flow rate of 0.2mL / min, and volume space velocity of 40h -1 After the system was stabilized, the product condensate was collected and the product composition was analyzed by GC-MS. The reaction results are shown in Table 3.
[0142] The conversion rate x of the reactant is calculated according to the following formula:
[0143]
[0144] Wherein, a is the mass fraction of 4,6-DMDBT or pyrene in the product, and b is the mass fraction of 4,6-DMDBT or pyrene in the raw material.
[0145] Table 3
[0146]
[0147]
[0148] Combining the above table and the data in the examples, it can be seen that in TiO 2Under the premise of the same content, when the aluminum oxide-titanium oxide composite oxide material prepared by the method provided by the present invention is used as a catalyst carrier to prepare a catalyst, the catalyst has good reaction activity and has good aromatic hydrogenation saturation performance while maintaining a high hydrodesulfurization activity.
[0149] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a hydrogenation catalyst, characterized in that: The method comprises the following steps: (1) subjecting an acidic solution containing aluminum and titanium to a colloid reaction with an alkaline solution containing aluminum to obtain a solid colloid product; (2) subjecting the solid gel-forming product obtained in step (1) to an aging reaction in the presence of a precipitant to obtain an aging reaction product; (3) subjecting the aging reaction product obtained in step (2) to a hydrothermal treatment, and then to a first drying to obtain titanium-containing pseudo-boehmite, wherein the temperature of the hydrothermal treatment is higher than the temperature of the aging reaction; (4) optionally shaping the titanium-containing pseudo-boehmite obtained in step (3), and then performing a second drying and a first calcination to obtain a titanium oxide-aluminum oxide composite oxide support; (5) Introducing active components and auxiliary agents onto the titanium oxide-aluminum oxide composite oxide carrier obtained in step (4), and then performing a third drying and a second calcination to obtain a hydrogenation catalyst, wherein the active components are selected from at least one of the Group VIII metals and at least one of the Group VIB metals, and the auxiliary agents are selected from at least one of the Group VA elements.
2. The method according to claim 1, wherein: In step (1), the acidic solution containing aluminum and titanium is prepared by dissolving a titanium-containing compound in an acidic aluminum solution; Preferably, the titanium-containing compound is titanyl sulfate and / or titanium sulfate; Preferably, the acidic aluminum solution is selected from at least one of an aluminum sulfate solution, an aluminum nitrate solution and an aluminum chloride solution; Preferably, in step (1), the aluminum-containing alkaline solution is a sodium aluminate solution and / or a potassium aluminate solution; Preferably, in step (1), the concentration of the acidic solution containing aluminum and titanium is 35-120 g / L in terms of alumina; Preferably, in step (1), the concentration of the acidic solution containing aluminum and titanium is 5-80 g / L in terms of titanium oxide; Preferably, in step (1), the concentration of the aluminum-containing alkaline solution is 20-300 g / L in terms of alumina.
3. The method according to claim 1 or 2, wherein: In step (1), the gelling reaction is carried out in a continuous or intermittent manner, preferably in a continuous manner; Preferably, in step (1), the conditions for the gelling reaction include: a temperature of 50-70° C. and a pH value of 4-7.
4. The method according to any one of claims 1 to 3, wherein: In step (2), the precipitant is selected from a compound containing an alkali metal, preferably at least one selected from sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate; Preferably, in step (2), the conditions of the aging reaction include: temperature of 60-98°C, time of 4-9h, pH value of 7-11; Further preferably, in step (2), the conditions of the aging reaction include: temperature of 70-95°C, time of 5-8h, and pH value of 7.5-10.
5. The method according to any one of claims 1 to 4, wherein: The temperature of the hydrothermal treatment is 10-100°C higher than the temperature of the aging reaction, preferably 10-80°C higher, more preferably 20-70°C higher; Preferably, the method does not use an organic titanium-containing reagent; Preferably, in step (3), the conditions of the hydrothermal treatment include: temperature 100-180° C., time 2-9 h.
6. The method according to any one of claims 1 to 5, wherein: In step (4), the first calcination conditions include: temperature of 300-800° C., time of 1-6 h; Preferably, in step (4), the conditions for the first calcination include: a temperature of 400-600° C. and a time of 2-4 h.
7. The method according to any one of claims 1 to 6, wherein: The amounts of the aluminum-titanium-containing acidic solution and the aluminum-containing alkaline solution are such that the aluminum oxide-titanium oxide composite oxide carrier prepared has an aluminum oxide content of 70-99% by weight, preferably 75-96% by weight, and a titanium oxide content of 1-30% by weight, preferably 4-25% by weight, based on the total amount of the aluminum oxide-titanium oxide composite oxide carrier; Preferably, the titanium oxide is anatase type, and the aluminum oxide is γ crystalline.
8. The method according to any one of claims 1 to 7, wherein: The alumina-titania composite oxide carrier has a pore volume of 0.4-1 mL / g and a specific surface area of 150-400 m 2 / g, the most probable pore size is 5-13nm; Preferably, the alumina-titania composite oxide carrier has a pore volume of 0.6-0.8 mL / g and a specific surface area of 200-300 m 2 / g, and the most probable pore size is 7-12nm.
9. The method according to any one of claims 1 to 8, wherein: In step (5), the active component is selected from cobalt and / or nickel and molybdenum and / or tungsten; And / or, in step (5), the auxiliary agent is phosphorus; Preferably, in step (5), the conditions for the second calcination include: a temperature of 200-700° C. and a time of 1-6 h; Further preferably, in step (5), the conditions for the second calcination include: a temperature of 300-500° C. and a time of 2-4 h.
10. The method according to any one of claims 1 to 9, wherein: The titanium oxide-aluminum oxide composite oxide carrier, active components and additives are used in such amounts that, in the prepared hydrogenation catalyst, based on the total amount of the hydrogenation catalyst, the content of the Group VIII metal in terms of oxide is 0.5-10% by weight, preferably 1.5-5% by weight, the content of the Group VIB metal in terms of oxide is 5-35% by weight, preferably 6-30% by weight, and the content of the Group VA element in terms of oxide is 1-6% by weight, preferably 2-5% by weight.
11. A hydrogenation catalyst obtained by the preparation method according to any one of claims 1 to 10.
12. Use of the hydrogenation catalyst according to claim 11 in a hydrodesulfurization reaction or an aromatics hydrogenation saturation reaction.
Citation Information
Patent Citations
Heavy distillate oil hydrotreating catalyst and application thereof
CN109833891A
Hydrotreating catalyst with a titanium containing carrier and organic additive
CN111050904A
Hydrogenation catalyst, preparation method and application thereof
CN113649016A
Hydrodesulfurization catalyst and preparation method thereof
CN112675828A
Heavy oil hydrodesulfurization catalyst and heavy oil hydrotreating method
CN114618511A